Dynamics of Designing and Implementing Social Safety Net Programmes in Developing Countries (Bangladesh Journal of Public Administration, 2019)
Social Safety Net as a part of social protection programmes is now very popular in many developing countries. Political discourses have a role in prioritizing and implementing such pro-poor policy. The objective of this paper is to understand the dynamics of political discourses that influences in adopting and sustaining Social Safety Net Programmes in these countries utilizing the common assumptions proposed by Hickey (2006) and Barrientos and Pellissery (2012). The analysis of this paper identifies that the assumptions developed by Hickey, Barrientos and Pellissery are not adequate enough to capture political discourses around SSNPs in the developing countries. These assumptions mainly help us to understand such discourses from the macro/structural perspective and fail to capture the politics at the micro level. The paper, therefore, argues for more rigorous empirical based research from cross-country perspective focusing both macro and micro level politics.